Supercritical Assisted Atomization: Polyvinylpyrrolidone as Carrier for Drugs with Poor Solubility in Water. (30th May 2013) - Liparoti, Sara; Adami, Renata; Caputo, Giuseppe; Reverchon, Ernesto
Abstract : Supercritical assisted atomization (SAA) is an efficient technique to produce microparticles and composite microspheres formed by polymers and pharmaceutical compounds. In this work polyvinylpyrrolidone (PVP) was proposed as carrier for pharmaceutical compounds that show a poor solubility in water medium. Indeed, this polymer is hydrosoluble and can be generally used to enhance the dissolution rate of hydrophobic compounds when finely dispersed in it. However, it is difficult to obtain coprecipitates with a uniform dispersion of the active molecule using other micronization techniques. The experiments were performed using ethanol as solvent; SAA plant was operated at 40°C and 76 bar in the saturator and 70°C and 1.6 bar in the precipitator. Three different dexamethasone/polymer weight ratios were selected: 1/2, 1/4, and 1/8. Produced composite particles showed a regular, spherical shape and a mean diameter ranging from about 0.8 to 1 μ m, depending on the polymer/drug weight ratio. Dissolution analysis demonstrated that microparticles containing a lower drug amount show a higher dissolution rate.